The United States' Regulatory Environment Is Evolving to Accommodate a Coming Boom in Gene Therapy Research. (September 2019) - Eisenman, Daniel
Introduction: A dramatic increase in the number of clinical trials involving gene-modified cell therapy and gene therapy is taking place. The field is on the verge of a boom, and the regulatory environment is evolving to accommodate the growth. Discussion: This commentary summarizes the current state of the field, including an overview of the growth. The United States (US) regulatory structure for gene therapy will be summarized, and the evolution of the oversight structure will be explained. Conclusion: The gene therapy field has recently produced its first FDA-approved therapeutics and has a pipeline of other investigational products in the final stages of clinical trials before they can be evaluated by the FDA as safe and effective therapeutics. As research continues to evolve, so must the oversight structure. Biosafety professionals and IBCs have always played key roles in contributing to the safe, evidence-based advancement of gene therapy research. With the recent regulatory changes and current surge in gene therapy research, the importance of those roles has increased dramatically.